2023
DOI: 10.3390/genes14091730
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Potentially Modulates the Expression of Key Onco- and Tumor Suppressor miRNAs in Prostate and Colon Cancer Cell Lines: Insights from PC3 and HCT-15 Cells

Sofía Madeline Osorio-Pérez,
Carolina Estrada-Meza,
Luis M. Ruiz-Manriquez
et al.

Abstract: Prostate cancer (PC) and colon cancer significantly contribute to global cancer-related morbidity and mortality. Thymoquinone (TQ), a naturally occurring phytochemical found in black cumin, has shown potential as an anticancer compound. This study aimed to investigate the effects of TQ on the expression profile of key tumor suppressor and onco-suppressor miRNAs in PC3 prostate cancer cells and HCT-15 colon cancer cells. Cell viability assays revealed that TQ inhibited the growth of both cell lines in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…CRC stands as a significant challenge for global healthcare systems, ranking as the third most frequently diagnosed cancer worldwide and representing the second leading cause of cancer-related deaths, affecting both men and women ( Lewandowska et al, 2022 ; Osorio-Pérez et al, 2023 ). Consequently, there is a dedicated focus on innovative approaches to cancer treatment, exploring new strategies and solutions ( Biller and Schrag, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRC stands as a significant challenge for global healthcare systems, ranking as the third most frequently diagnosed cancer worldwide and representing the second leading cause of cancer-related deaths, affecting both men and women ( Lewandowska et al, 2022 ; Osorio-Pérez et al, 2023 ). Consequently, there is a dedicated focus on innovative approaches to cancer treatment, exploring new strategies and solutions ( Biller and Schrag, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that TQ potentiates cisplatin-induced cell death in a dose-dependent manner, indicating a potential role for TQ in augmenting the chemosensitivity of colon cancer cells [ 129 ]. Research conducted by Osorio-Pérez demonstrated a significant reduction in the expression levels of miR-21-5p in HCT-15 cells following TQ treatment [ 130 ]. Interestingly, the combination of TQ with ionizing radiation (IR) enhanced cytotoxicity against HT-29 and HCT-116 cells.…”
Section: Tq and Colorectal Cancermentioning
confidence: 99%
“…The growth of HCT-15 cells was observed to be suppressed by TQ in a dose-dependent manner (IC 50 : 82.59 µM). Furthermore, the growth of these cells was adversely affected even when exposed to higher doses of TQ [ 130 ]. TQ with ionizing radiation caused G2/M arrest in HT-29 and HCT-116 cells.…”
Section: Tq and Colorectal Cancermentioning
confidence: 99%